Evaluation of Family Knowledge in Detecting Risk of Diabetes Foot Ulcer in Public Health Center - Sarina Musdiaman; Saldy Yusuf; Titi Iswanti Afelya; Nurul Hidayah (Faculty of Nursing, Universitas Hasanuddin, 2020)
Introduction: Diabetes Foot Ulcer (DFU) is one of the most common DM complications, due to several factors including lack of knowledge in foot care, maladaptive behaviors in preventing DFU, and inadequate of education to the community related to the detection of DFU. This study aimed to evaluate family knowledge in detecting the risk DFU in public health centres. Method: This is a quantitative research used descriptive research methods. The instrument used was a questionnaire that consisted of 10 question items. The sample in this study was 40 families and have been educated in the previous studies. Results: The result of this study stated that family knowledge related detection of risk of DFU more better in younger compare to elderly (25% vs 2.5%), and mainly house wife has a good ability in knowledge Conclusions: Family knowledge related to the detection of DFU consider good.